Exploring the Role of School Principals in Enhancing Literacy Culture in South Aceh Public High Schools - Aslinar; Nasir Usman; Khairuddin (International Journal of Educational and Life Sciences, 2025)
This study explores the role of school principals in developing a literacy culture in public high schools (SMAN) in South Aceh. The research adopts a qualitative descriptive approach to examine the leadership strategies employed by principals to foster literacy, the challenges they face, and the solutions they implement. Data were collected through observations, interviews, and document analysis involving principals, teachers, and students from three high schools actively engaged in literacy programs. The findings reveal that school principals play a critical role in promoting literacy by implementing structured reading programs, enhancing library resources, and integrating digital tools to engage students. However, significant challenges, such as limited funding, inadequate library infrastructure, and low student motivation, were identified. To address these obstacles, principals employed innovative solutions, including book donation drives, partnerships with local libraries, and increased parental involvement. Despite these challenges, the study shows that the principals' leadership strategies have positively impacted students' literacy engagement, with reported increases in reading habits and participation in literacy activities. The research concludes that effective school leadership, supported by community partnerships and modern digital approaches, is essential for fostering a strong literacy culture in resource-constrained environments.